Divergent responses of tiller and grain yield to fertilization and fallow precipitation: Insights from a 28-year long-term experiment in a semiarid winter wheat system - Rui WANG; Ying WANG; Ya-xian HU; Ting-hui DANG; Sheng-li GUO (Journal of Integrative Agriculture, 2021)
Tillering is an important phenological stage, which is strongly related to the yield in spike components and final grain yield during winter wheat growth. Precipitation during the fallow season (fallow precipitation) influences tillering in winter wheat on the semi-arid Chinese Loess Plateau. However, little work has been done regarding tiller number changes under various types of fertilization and amounts of fallow precipitation on a long-term scale. Effects of fallow precipitation and fertilization on tiller were investigated in a winter wheat (Triticum aestivum L.) system in a 28-year field study (1990 to 2017) in a semiarid agro-ecosystem. Tiller number, spike number and grain yield were measured in four fertilization conditions: control without fertilizer (CK); mineral nitrogen fertilizer alone (N); mineral phosphorus fertilizer alone (P); mineral nitrogen and phosphorus fertilizer together (NP). Based on the long-term annual fallow precipitation, dry years (<mean annual fallow precipitation) and wet years (>mean annual fallow precipitation) were distinguished. Phosphorus fertilization alone significantly increased the mean annual tiller number (23%), and the increase in tiller number was higher in wet years (29%) than in the dry years (17%). However, nitrogen fertilization alone had little effect on mean tiller number, while nitrogen and phosphorus together significantly increased mean annual tiller number (30%), mean tiller number in wet years (45%) and mean tiller number in dry years (17%). Tiller number was significantly and positively correlated with fallow precipitation in dry years for all fertilizer treatments, whereas it was weakly and either positively or negatively correlated with fallow precipitation in wet years depending on the treatment. This study found positive correlations between tiller number and fallow precipitation in the CK and NP treatments, and it found negative correlations between tiller number and fallow precipitation in the treatments with nitrogen fertilization alone or phosphorous fertilization alone in wet years. Understanding the impacts of fallow precipitation and fertilization on tiller development shed light on ways to improve crop production in rain-fed agricultural regions.